Estimated cardiovascular relative risk reduction from fixed-dose combination pill (polypill) treatment in a wide range of patients with a moderate risk of cardiovascular disease. (29th August 2020) - Lafeber, Melvin; Webster, Ruth; Visseren, Frank LJ; Bots, Michiel L; Grobbee, Diederick E; Spiering, W; Rodgers, Anthony; ,
Abstract: Aims: Recent data indicate that fixed-dose combination (FDC) pills, polypills, can produce sizeable risk factor reductions. There are very few published data on the consistency of the effects of a polypill in different patient populations. It is unclear for example whether the effects of the polypill are mainly driven by the individuals with high individual risk factor levels. The aim of the present study is to examine whether baseline risk factor levels modify the effect of polypill treatment on low-density lipoprotein (LDL)-cholesterol, blood pressure (BP), calculated cardiovascular relative risk reduction and adverse events. Methods: This paper describes a post-hoc analysis of a randomised, placebo-controlled trial of a polypill (containing aspirin 75 mg, simvastatin 20 mg, lisinopril 10 mg and hydrochlorothiazide 12.5 mg) in 378 individuals without an indication for any component of the polypill, but who had an estimated five-year risk for cardiovascular disease ≥7.5%. The outcomes considered were effect modification by baseline risk factor levels on change in LDL-cholesterol, systolic BP, calculated cardiovascular relative risk reduction and adverse events. Results: The mean LDL-cholesterol in the polypill group was 0.9 mmol/l (95% confidence interval (CI): 0.8–1.0) lower compared with the placebo group during follow-up. Those with a baseline LDL-cholesterol >3.6 mmol/l achieved a greater absolute LDL-cholesterol reduction with the polypill compared with placebo, than patients with an LDL-cholesterol ≤3.6 mmol/l (−1.1 versus −0.6 mmol/l, respectively). The mean systolic BP was 10 mm Hg (95% CI: 8–12) lower in the polypill group. In participants with a baseline systolic BP >135 mm Hg the polypill resulted in a greater absolute systolic BP reduction with the polypill compared with placebo, than participants with a systolic BP ≤ 135 mm Hg (−12 versus −7 mm Hg, respectively). Calculated from individual risk factor reductions, the mean cardiovascular relative risk reduction was 48% (95% CI: 43–52) in the polypill group. Both baseline LDL-cholesterol and estimated cardiovascular risk were significant modifiers of the estimated cardiovascular relative risk reduction caused by the polypill. Adverse events did not appear to be related to baseline risk factor levels or the estimated cardiovascular risk. Conclusion: This study demonstrated that the effect of a cardiovascular polypill on risk factor levels is modified by the level of these risk factors. Groups defined by baseline LDL-cholesterol or systolic BP had large differences in risk factor reductions but only moderate differences in estimated cardiovascular relative risk reduction, suggesting also that patients with mildly increased risk factor levels but an overall raised cardiovascular risk benefit from being treated with a polypill.